Kinerja Dinas Satuan Polisi Pamong Praja Kota Palu - Filo Leonardo Tinggogoy; Ahlan Ahlan (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2020)
The performance of employee is the achievement to what extent that employee able to do a good job based on work implementation. Generally, local government institution does not apply based on work performance, but only routinely. Works implication that obtained are not satisfactory in achievement employee performance. This research about how the employee do their works routinely in institutional that required to have quality human resources, and have firmness to able to do the duty that be imposed as rule enforces. This research got the data from the informant that related to this job directly and secondary data from the information in several related institutions. The result of this research show that the law of enforcement needs the optimal power source, that have done well by institutional apparatus.